An in silico approach to develop potential therapies against Middle East Respiratory Syndrome Coronavirus (MERS-CoV) - Suvro Biswas; Mohasana Akter Mita; Shamima Afrose; Md. Robiul Hasan; Mst. Sharmin Sultana Shimu; Shahriar Zaman; Md. Abu Saleh (Heliyon, 2024)
A deadly respiratory disease Middle East Respiratory Syndrome (MERS) is caused by a perilous virus known as MERS-CoV, which has a severe impact on human health. Currently, there is no approved vaccine, prophylaxis, or antiviral therapeutics for preventing MERS-CoV infection. Due to its inexorable and integral role in the maturation and replication of the MERS-CoV virus, the 3C-like protease is unavoidly a viable therapeutic target. In this study, 2369 phytoconstituents were enlisted from Japanese medicinal plants, and these compounds were screened against 3C-like protease to identify feasible inhibitors. The best three compounds were identified as Kihadanin B, Robustaflavone, and 3-beta-O- (trans-p-Coumaroyl) maslinic acid, with binding energies of −9.8, −9.4, and −9.2 kcal/mol, respectively. The top three potential candidates interacted with several active site residues in the targeted protein, including Cys145, Met168, Glu169, Ala171, and Gln192. The best three compounds were assessed by in silico technique to determine their drug-likeness properties, and they exhibited the least harmful features and the greatest drug-like qualities. Various descriptors, such as solvent-accessible surface area, root-mean-square fluctuation, root-mean-square deviation, hydrogen bond, and radius of gyration, validated the stability and firmness of the protein-ligand complexes throughout the 100ns molecular dynamics simulation. Moreover, the top three compounds exhibited better binding energy along with better stability and firmness than the inhibitor (Nafamostat), which was further confirmed by the binding free energy calculation. Therefore, this computational investigation could aid in the development of efficient therapeutics for life-threatening MERS-CoV infections.